SOX7 transcription factor: sequence, chromosomal localisation, expression, transactivation and interference with Wnt signalling - Takash, Wafaa (Oxford University Press, 2001)
The Sox gene family consists of several genes related by encoding a 79 amino acid DNA-binding domain known as the HMG box. This box shares strong sequence similarity to that of the testis determining protein SRY. SOX proteins are transcription factors having critical roles in the regulation of diverse developmental processes in the animal kingdom. We have characterised the human SOX7 gene and compared it to its mouse orthologue. Chromosomal mapping analyses localised mouse Sox7 on band D of mouse chromosome 14, and assigned human SOX7 in a region of shared synteny on human chromosome 8 (8p22). A detailed expression analysis was performed in both species. Sox7 mRNA was detected during embryonic development in many tissues, most abundantly in brain, heart, lung, kidney, prostate, colon and spleen, suggesting a role in their respective differentiation and development. In addition, mouse Sox7 expression was shown to parallel mouse Sox18 mRNA localisation in diverse situations. Our studies also demonstrate the presence of a functional transactivation domain in SOX7 protein C-terminus, as well as the ability of SOX7  protein to significantly reduce Wnt/β-catenin-stimulated transcription. In view of these and other findings, we suggest different modes of action for SOX7 inside the cell including repression of Wnt signalling.